The Controversy over the Registration of Interfaith Marriages: A Conflict between Human Rights and Islamic Law - Amilia, Fatma; Chasanah, Nur (UIN Sunan Kalijaga Yogyakarta, 2025)
This article examines the emerging judicial trend in Indonesia concerning the registration of interfaith marriages, particularly through the application of the concept of submission to a single religious law. On the one hand, this practice is often justified as an effort to accommodate human rights and administrative legal certainty. On the other hand, it raises fundamental normative tensions with Islamic law. This study takes as its primary case the Decision of the Yogyakarta District Court Number 378/Pdt.P/2022/PN.Yyk. Employing a qualitative legal research method, the study analyzes official court documents and relevant statutory regulations, jurisprudence, and scholarly literature. The findings reveal that the authorization of interfaith marriage registration by civil courts is largely based on jurisprudence developed by the Supreme Court, which recognizes the validity of such marriages when one party submits to the religious law of the other. This approach has been further institutionalized through an official circular letter issued by the Supreme Court. However, from the perspective of Islamic jurisprudence (fiqh), this concept is highly problematic. Islamic law adheres to the principle that the original legal status of marriage is prohibition, and permissibility arises only when all substantive and formal religious requirements are fulfilled. Consequently, the performance or registration of a marriage outside Islamic law cannot replace its normative authority. An interfaith union involving a Muslim that is not solemnized according to Islamic law cannot be regarded as a valid marriage, but merely as a biological relationship without legitimate marital status. Artikel ini mengkaji kecenderungan yudisial yang berkembang di Indonesia terkait pencatatan perkawinan beda agama, khususnya melalui penerapan konsep ketundukan pada satu hukum agama. Di satu sisi, praktik ini kerap dibenarkan sebagai upaya untuk mengakomodasi hak asasi manusia dan menjamin kepastian hukum administrasi. Namun, di sisi lain, praktik tersebut menimbulkan ketegangan normatif yang mendasar dengan hukum Islam. Penelitian ini menggunakan Putusan Pengadilan Negeri Yogyakarta Nomor 378/Pdt.P/2022/PN.Yyk sebagai studi kasus utama. Dengan menggunakan metode penelitian hukum kualitatif, kajian ini menganalisis dokumen putusan pengadilan, peraturan perundang-undangan yang relevan, yurisprudensi, serta literatur ilmiah. Hasil penelitian menunjukkan bahwa pemberian izin pencatatan perkawinan beda agama oleh pengadilan sipil terutama didasarkan pada yurisprudensi yang dikembangkan oleh Mahkamah Agung, yang mengakui keabsahan perkawinan tersebut apabila salah satu pihak tunduk pada hukum agama pihak lainnya. Pendekatan ini selanjutnya dilembagakan melalui surat edaran resmi Mahkamah Agung. Namun demikian, dari perspektif fikih, konsep tersebut dipandang bermasalah. Hukum Islam menganut prinsip bahwa status hukum asal perkawinan adalah terlarang, dan kebolehan baru muncul apabila seluruh syarat substantif dan formal keagamaan terpenuhi. Oleh karena itu, pelaksanaan atau pencatatan perkawinan di luar hukum Islam tidak dapat menggantikan otoritas normatifnya. Perkawinan beda agama yang melibatkan seorang Muslim dan tidak dilangsungkan sesuai dengan hukum Islam tidak dapat dianggap sebagai perkawinan yang sah, melainkan semata-mata sebagai hubungan biologis tanpa ikatan perkawinan yang sah.